Pengaruh Inovasi Produk Dan Citra Rasa Terhadap Meningkatkan Daya Saing Umkm Dengan Variabel Moderasi Merek (Studi Kasus Usaha Bolu Karamel Pasundan di Kota Rantauprapat) - Wilda Hasanah; Zulkarnain Nasution; Nova Jayanti Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but often face competitive challenges, particularly in the bakery sector. This study aims to analyze the influence of product innovation and taste on MSME competitiveness, with brand as a moderating variable, in a case study of Pasundan Caramel Cake in Rantauprapat City. The study used a descriptive quantitative approach with 96 respondents selected throughpurposive samplingbased on the Lemeshow formula. Data were collected through a Likert-scale questionnaire and observation, then analyzed usingStructural Equation ModelingbasedPartial Least Square(SEM-PLS) with the help of SmartPLS. The results showed that product 1).innovation had a significant effect on brand. 2).Taste image also had a significant effect on brand. 3). Brand had a significant effect on competitiveness. 6).The indirect effect of product innovation on competitiveness through branding was significant, while the effect of taste image through branding was insignificant.7). The research model had an R² value of 0.925 for branding and 0.962 for competitiveness, indicating very strong predictive ability. These findings confirm that product innovation, taste image, and brand strengthening together contribute significantly to increasing the competitiveness of bakery MSMEs. Strategies that integrate product creativity, taste consistency, and brand identity are expected to strengthen the position of MSMEs in a competitive market.